PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP INTENSITAS MEROKOK PADA SISWA - Arif Nurma Etika; Dwi Septian Wijaya (Care : Jurnal Ilmiah Ilmu Kesehatan, 2015)
Smoking is an activity that causes a lot of health problems. Spiritual Emotional Freedom Technique (SEFT) allegedly can be used as complementary therapy for reduce smoking intensity by tapping on the 18 key points along the body. This study aimed to determine the effect of SEFT on smoking intensity at students of SMAN 5 Kediri City in 2015. The method used was a pre-experimental, with a pretest and posttest design. In this study, respondents were grouped into one group intervention (n=14). In this group performed pretest to determine the level of smoking intensity, the intervention group was given nine SEFT therapy sessions (each sessions 20 minutes). At the end of the third week performed post-test in this group. In this study it was found that the pretest in this group showed mild smoking intensity. In the posttest, intervention group shows reduction of mild smoking intensity became light smoking intensity (50%). By Wilcoxon test obtained, the p value of smoking intensity 0.003